2006
DOI: 10.1515/crelle.2006.097
|View full text |Cite
|
Sign up to set email alerts
|

Non-archimedean amoebas and tropical varieties

Abstract: Abstract. We study the non-archimedean counterpart to the complex amoeba of an algebraic variety, and show that it coincides with a polyhedral set defined by Bieri and Groves using valuations. For hypersurfaces this set is also the tropical variety of the defining polynomial. Using non-archimedean analysis and a recent result of Conrad we prove that the amoeba of an irreducible variety is connected. We introduce the notion of an adelic amoeba for varieties over global fields, and establish a form of the local-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
275
0
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(281 citation statements)
references
References 21 publications
1
275
0
5
Order By: Relevance
“…This was introduced by Bergman [3], and then Bieri and Groves [4] showed that the cone over it was a rational polyhedral fan. Later work of Kapranov [5], and then Speyer and Sturmfels [19] identified this fan with the negative − Trop(X) of the tropical variety of X, computed in any valued field K containing C with valuation group Γ and residue field C. Here is the solution of these inequalities, the amoeba A (ℓ), and the tropical variety Trop(ℓ). The coamoeba coA (X) of a subscheme X of T N is the image of X(C) under the argument map Arg.…”
Section: 4mentioning
confidence: 99%
“…This was introduced by Bergman [3], and then Bieri and Groves [4] showed that the cone over it was a rational polyhedral fan. Later work of Kapranov [5], and then Speyer and Sturmfels [19] identified this fan with the negative − Trop(X) of the tropical variety of X, computed in any valued field K containing C with valuation group Γ and residue field C. Here is the solution of these inequalities, the amoeba A (ℓ), and the tropical variety Trop(ℓ). The coamoeba coA (X) of a subscheme X of T N is the image of X(C) under the argument map Arg.…”
Section: 4mentioning
confidence: 99%
“…One may also define amoebas for varieties over fields other than ‫.ރ‬ Amongst other results on varieties over non-Archimedean fields, Kapranov gave a description of their amoebas in term of polyhedral complexes in ‫ޒ‬ n [4]. Mikhalkin then used this description in order to obtain new results about the topology of complex hypersurfaces [15].…”
Section: Introductionmentioning
confidence: 99%
“…A consequence of an important result due to Kapranov [10] is that the set T 1 ∩ T 2 contains the image under the valuation map (see Sect. 2.1) of the solutions to (1.4).…”
Section: Theorem 11 There Exists a Real System (11) Of Two Polynomimentioning
confidence: 99%